Scientific trends in nursing of ergonomy (Research, Society and Development, 2022)
This one article aims to analyze trends in scientific studies regarding the ergonomics of nursing professionals; to know the prevalent risks in the midst of the nursing team's work activities and to identify the most prevalent ergonomic class in the studies. For this research, the integrative literature review, which allows for a inspection complex scientific production produced in a given period. The results obtained were 06 productions that pointed out a certain literary scarcity regarding the proposed theme, but it was possible to identify that scientific trends are concentrated in risks to which professionals are exposed, as well as the impacts on workers' health, the main ergonomic classes, with cognitive ergonomics not very significant. As for the risks present in the work environment were: biological, physical and ergonomic. Regarding the ergonomic class, physics was the most prevalent. So, in view of the results obtained, it is worth highlighting the need to encourage future investigations, especially regarding cognitive ergonomics in the context of nursing, with the objective of contributing to the physical and psychological well-being of the worker, enabling them to better health conditions occupational, work performance, effective decision-making in health care.